Threat Sensitivity and Fear of Cancer Recurrence: A Daily Diary Study of Reactivity and Recovery as Patients and Spouses Face the First Mammogram Post-Diagnosis - Soriano, Emily C. (J Psychosoc Oncol, 2018)
OBJECTIVES: Fear of cancer recurrence (FCR) is a top concern of breast cancer (BC) survivors and their spouses, yet little is known about responses to FCR triggers in daily life. We examined whether a biologically-based individual difference—threat sensitivity—predicted FCR in couples facing the first post-diagnosis mammogram (MMG). We hypothesized that threat sensitivity would predict greater FCR reactivity before the MMG and higher peak FCR on the MMG day, controlling for global anxiety. We also explored the link between threat sensitivity and FCR recovery after MMG. DESIGN AND SAMPLE: Fifty-seven early-stage BC patients and their spouses completed cross-sectional measures of threat sensitivity and global anxiety. Couples then reported daily FCR during a three-week diary period that began two weeks before the patient’s MMG appointment. METHODS: Multilevel actor-partner interdependence modeling was used to estimate within-person random slopes of FCR before (reactivity) and after (recovery) the MMG. Random intercepts captured individual differences in peak FCR on the MMG day. Patient and spouse threat sensitivity and anxiety were entered as predictors of reactivity, peak, and recovery. FINDINGS: FCR increased leading to MMG; however, inconsistent with hypotheses, this reactivity was not significantly predicted by threat sensitivity. Actor, but not partner, effects for peak FCR emerged, such that patients and spouses with greater threat sensitivity had greater FCR on the MMG day. FCR decreased after the MMG, and spouse, but not patient, threat sensitivity predicted slower recovery for both partners. CONCLUSIONS: Findings lend preliminary support for the role of threat sensitivity in the experience of FCR as couples confront threatening events in BC survivorship. IMPLICATIONS FOR PSYCHOSOCIAL PROVIDERS: MMGs can be a triggering event for couples. Threat sensitivity may help identify those who are likely to experience elevations in FCR during this stressful period.